Electron Impact Ionization Cross Sections of $C_2H_2$ and $CH$ Molecules at Low and High Energy Range (Journal of Atomic and Molecular Sciences, 2010)
In this communication, studies of the total ionization cross sections of hydrocarbon molecules ($CH,$ $C_2H_2$) due to electron impact are presented. Electron impact ionization cross sections (EIICS) have been calculated from threshold ionization energy to high energy (10 MeV). Apart from EIICS calculation the values of collisional parameters are also calculated. The theoretical model, developed by Khare, has been modified to calculate the total ionization cross section for molecules. Obtained theoretical cross sections are compared extensively with a number of experimental and theoretical data. The obtained values of collisional parameter compared with the available experimental values.